Can phenotypic selection on floral traits explain the presence of enigmatic intermediate individuals in sympatric populations of Platanthera bifolia and P. chlorantha (Orchidaceae)?. Issue 1 (10th November 2019) - Ambroise, Valentin; Esposito, Fabiana; Scopece, Giovanni; Tyteca, Daniel
Abstract: Pollinators represent one of the main agents of selection on floral traits. Here, we estimated phenotypic selection on floral morphology and phenology in a sympatric population of two orchid species, Platanthera bifolia and P. chlorantha, including enigmatic individuals with intermediate column morphology (as reflected by the distance between viscidia and caudicle length, two traits involved in assortative mating and reproductive isolation among Platanthera species), but genetically indistinguishable from P. bifolia . Our aim was to clarify whether the occurrence of intermediate phenotypes could be explained by the presence of selective pressures exerted by pollinators. Simple linear and quadratic regressions together with univariate and multivariate analyses were used to evaluate the strength of directional, disruptive and stabilizing selection. We found that selection on phenotypic traits varied between groups and sex functions. Contrary to our hypothesis, selection on the viscidia distance and caudicle length appeared to be consistent in the two P. bifolia groups. Interestingly, the viscidia distance was under significant stabilizing selection through female reproductive success in intermediate individuals. Based on these results, we conclude that, despite a significant selective pressure on some phenotypic traits, the presence of individuals with intermediate phenotype is not due to selection. Stabilizing selection on distance between viscidia in intermediate individuals may suggest that assortative mating play a role in the maintenance of this phenotypic polymorphism. Abstract : Our aim was to clarify whether the occurrence of enigmatic intermediate phenotypes (in turquoise) between two related orchid species growing in sympatry (Platanthera bifolia, in blue, and P. chlorantha, in red) could be explained by the presence of selective pressures on floral traits exerted by pollinators. We found that, despite a significant selective pressure on some phenotypic traits, the presence of individuals with intermediate phenotype is not due to selection. Each horizontal line represents an individual plant and is drawn from the day the first flower opened to the day the last flower opened, sorted first by opening date of the first flower and then by flowering duration. Black dots represent the total number of inflorescences with at least one flower open for each recording time.